An integrated hydro-economic modelling framework to evaluate water allocation strategies I: model development - George, B.A.; Malano, H.M.M.; Davidson, B.; Hellegers, Petra J.G.J.; Bharati, Luna; Massuel, S. (Elsevier, 2011)
In this paper an integrated modelling framework for water resources planning and management that can be used to carry out an analysis of alternative policy scenarios for water allocation and use is described. The modelling approach is based on integrating a network allocation model (REALM) and a social Cost Benefit economic model, to evaluate the physical and economic outcomes from alternative water allocation policies in a river basin or sub-basin. From a hydrological perspective, surface and groundwater models were first applied to assess surface and groundwater resource availability. Then an allocation model was applied to reconcile the calculated surface and groundwater resources. From an economic perspective initially the value of water allocated to different uses in each demand centre within the system was estimated. These values were then placed in a social Cost Benefit Analysis to assess the economic consequences of different allocation scenarios over time and space. This approach is useful as it allows policymakers to consider not only the physical dimensions of distributing water, but also the economic consequences associated with it. This model is considered superior to other models as water is increasingly being seen as an economic good that should be allocated according to its value. The framework outlined in this paper was applied to the Musi sub-basin located in the Krishna Basin, India. In applying this framework it was concluded that competition for Musi water is very high, the transfer of water from agriculture to urban users is likely to grow in future and the value of water used in different agricultural zones is very low.